ACCOUNTING STUDENTS' PERCEPTIONS AND EDUCATIONAL ACCOUNTANTS ON ETHICS OF PREPARING FINANCIAL STATEMENTS - Endah Nurhawaeny Kardiyati; Abdul Karim (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The issue of Good Corporate Governance in Indonesia is still hotly discussed because it is considered a factor that can restore investor confidence. One of the components of Corporate Governance is the existence of transparent financial reporting. The ethics and positive attitude of Indonesian accountants as the point of emphasis of this study are one of the factors for improving the quality of financial reporting. This study used a purposive sampling method and obtained two groups of samples, accounting students and teaching accountants at public and private universities in the city of Semarang. The technical analysis to test the hypothesis using non-parametric statistics Kruskal Wallis. The results of hypothesis testing show that there is no difference between public accounting firm auditors, accounting students, and educating accountants regarding the attributes of knowledge, problem-solving skills, past experiences, responsiveness to situations, self-confidence, adaptability, having relevant knowledge, being able to be responsible and able to think fast. Meanwhile, the attributes of communication skills and thinking skills proved to be different between auditors of public accounting firms, accounting students, and teaching accountants. Overall the results of the research do not fully support the convergence theory. Keywords: Convergence Theory, Professionalism, Competence